Z doświadczeń nauczyciela przedszkola = From the experience of a kindergarten teacher - Kuczak, Ewa; Osiewicz, Adriana (Zielona Góra: Uniwersytet Zielonogórski, Wydział Pedagogiki, Psychologii i Socjologii)
In the article, the author gives an overview of the educational and didactic work of their nursery school. They share their experiences and reflections of everyday work in nursery school. (among other: projects, innovations, therapeutic activities).
Keywords: edukacja przedszkolna; dziecko; przedszkole; projekt; innowacja; pre-school education; child; kindergarten; project; innovation